2021
DOI: 10.3390/sym13112082
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Depot Joint Distribution Vehicle Routing Problem Considering Energy Consumption with Time-Dependent Networks

Abstract: This paper studies the multi-depot joint distribution vehicle routing problem considering energy consumption with time-dependent networks (MDJDVRP-TDN). Aiming at the multi-depot joint distribution vehicle routing problem where the vehicle travel time depends on the variation characteristics of the road network speed in the distribution area, considering the influence of the road network on the vehicle speed and the relationship between vehicle load and fuel consumption, a multi-depot joint distribution vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Finally, it was concluded that joint distribution between multi-logistics enterprises can more effectively reduce costs. Hou et al [14] have studied the multi-yard joint distribution vehicle routing problem under a time-varying network considering energy consumption, established a multi-yard joint distribution vehicle routing optimization model, and verified the effectiveness of the designed algorithm through multiple sets of numerical examples at different scales. Zheng et al [15] have discussed the cooperative vehicle routing problem in the urban logistics network during the COVID-19 pandemic, considering the order exchange distribution mode in the outer ring of the city, and established a multi-commodity mixed integer planning problem, which verified that this model can effectively improve transportation under traffic restrictions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, it was concluded that joint distribution between multi-logistics enterprises can more effectively reduce costs. Hou et al [14] have studied the multi-yard joint distribution vehicle routing problem under a time-varying network considering energy consumption, established a multi-yard joint distribution vehicle routing optimization model, and verified the effectiveness of the designed algorithm through multiple sets of numerical examples at different scales. Zheng et al [15] have discussed the cooperative vehicle routing problem in the urban logistics network during the COVID-19 pandemic, considering the order exchange distribution mode in the outer ring of the city, and established a multi-commodity mixed integer planning problem, which verified that this model can effectively improve transportation under traffic restrictions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, their model only considered one distribution center. With the development of sharing economy concept, collaboration among multiple distribution centers becomes a future direction (Hou et al ., 2021). Hence, this study proposes an electric vehicle routing problem considering multiple distribution centers under time-varying electricity prices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2021, China's production of new energy vehicles reached 3.677 million units, up 152.5 percent from the previous year [2]. Islamic research results show that when the fleet consists of only conventional vehicles, the average CO 2 emission increases by 13.58% compared to the mixed-fleet vehicle model [4]. In the "China Logistics Industry Investment Promotion Report 2015-2016", jointly released by the Ministry of Commerce and Deloitte, it is pointed out that China's reverse logistics market will exceed CNY 2 trillion in market capacity from Sustainability 2022, 14, 6613 2 of 27 2016 to 2020, and the proportion of the entire social logistics system will be more than 20% [5].…”
Section: Introductionmentioning
confidence: 99%
“…Ferro et al took into account the total mass of the vehicle, the gradient of the terrain, the travel speed that affects the rolling and aerodynamic resistance, and other factors to establish a detailed models of electric vehicle dynamic energy consumption [12]. Hou et al established a traditional vehicle fuel consumption model considering the weight of fuel vehicles loaded with cargo [13]. Li et al considered factors such as different speeds, loads, and distances in different road sections to build a dynamic energy consumption model for electric vehicles [14].…”
Section: Introductionmentioning
confidence: 99%